Dividend Taxation and the Cost of New Share Issues - Tobias Lindhe; Jan Södersten (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper examines how the effects of dividend taxation on the cost of new equity funds depend on whether or not shareholders can recover their original equity injections without being subject to the dividend tax. We point out the alternative assumptions in the literature on this, and we compare two different tax regimes, one where it is impossible for the firm to pay cash to its shareholders that is not taxed as dividends, the other where the shareholders are allowed a tax-free return of the original capital contributed through new issues. We conclude that any model, which explicitly or implicitly assumes that the shareholders cannot recover their original equity injections without being subject to the dividend tax, exaggerates the distortive effects of the tax.
Keywords: H24; H25; H32; 330; dividend taxation; return of capital; share repurchases; equity trap; cost of capital; nucleus theory; growth path